A Comparative Study of Ileostomy Versus Primary Repair of Enteric Perforation in Patients (Medical Forum Monthly, 2024)
Objective: To compare the outcome of primary repair of perforation with ileostomy in patients presenting with enteric perforation.Study Design: Randomized control trialPlace and Duration of Study: This study was conducted at the Department of General Surgery, M. Islam Medical & Dental College, Gujranwala from March 2017 to February 2018.Methodology: Eighty patients between 20-60 years of age and diagnosed as case of typhoid perforation. Patients were divided into two groups, Group A (Primary repair) and Group B (Ileostomy).The patients were observed for the development of complications during their hospital stay and follow up was done one week after discharge.Results: The mean age was 31.21±9.54 years of patient in group A and in group B was 32.42±10.25. Male to female ratio was 1.66:1 in group A and 2.07:1 in group B. The complications like wound infection was (25%) in group A and (45%) in group B, wound dehiscence was (10%) in group A and (17.5%) in group B and septicemia was (5%) in group A and (15%) in group B.Conclusion: Primary repair of the perforation is a better procedure than temporary ileostomy in enteric perforation due to its cost effectiveness and absence of complications related to ileostomy.